Our experience of spinal dural arteriovenous fistula: 4 case reports - Zeynep Ezgi Balçık (Türk Beyin Damar Hastalıkları Dergisi, 2017)
Spinal dural arteriovenous fistula, which is caused by the low flow shunts between dural arteries and the perimedullary venous system shows progressive myelopathy signs. It is usually found in the thoracic region. It is vital to accurately make differential diagnosis since the disease may cause irreversible injury. In this case report we aimed to discuss four cases of spinal arteriovenous fistula that showed different outcomes.